A study of the biology and control of the western flower thrips, Frankliniella occidentalis Pergande - Badenhorst, Jacqueline Anne (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1996.